Nonmonotonic energy dependence of net-proton number fluctuations - STAR Collaboration (Physical Review Letters, 2021)
Nonmonotonic variation with collision energy (sNN) of the moments of the net-baryon number distribution in heavy-ion collisions, related to the correlation length and the susceptibilities of the system, is suggested as a signature for the quantum chromodynamics critical point. We report the first evidence of a nonmonotonic variation in the kurtosis times variance of the net-proton number (proxy for net-baryon number) distribution as a function of sNN with 3.1 σ significance for head-on (central) gold-on-gold (Au+Au) collisions measured solenoidal tracker at Relativistic Heavy Ion Collider. Data in noncentral Au+Au collisions and models of heavy-ion collisions without a critical point show a monotonic variation as a function of sNN. © 2021 American Physical Society.
101 citations (Crossref) [2023-10-31] tex.art_number: 092301 tex.coden: PRLTA tex.document_type: Article tex.pubmed_id: 33750161 tex.source: Scopus
Keywords: Colliding beam accelerators; Collision energies; Correlation lengths; Gold; Hadrons; Heavy ion collision; Heavy ions; Ion sources; Monotonic variations; Non-monotonic variation; Number fluctuations; Quantum chromodynamics; Quantum theory; Relativistic Heavy Ion Collider; dept.phy; peer-reviewed